The Role of Music on The È‚yin Ceremony of the Mevlevi Tariqa - Shokouhi, Mohammad Ali; Yusof, Abdullah; Ali @ Mat Zin, Aizan (Online Journal of Research in Islamic Studies, 2018)
Mevlevi Tariqa has been formed under the influence of Mevlānā Jalāl al-Din Rumi. After Mevlānā his thinking penetrated in the Mevlevis path among his followers, and later on, the mystical and spiritual concepts were gradually mixed with music and became parts of the category of Mevlevis customs and traditions. In this way, Music in this Tariqa has been formed along with mystical rituals and dance based on Mevlānā’s Persian poems which is known Samā،. Along with development of Mevlevi Tariqa and formation of Mevlevi-khāna (Mevlevi house) in different cities, the primitive form of Samā، gradually turned to the ceremonial form of muqābala which also known as āyin. In fact, when the Samā، took the shape of āyin, the spiritual influence of music was started with all its traits. The Mevlevi āyin may be described as a form of worship, and music is one of the main mystical and spiritual elements of the ritual. Thus, the focus of this research is the role of Music in terms of theory and practice, as well as its mystical philosophy and functionality on performing āyin. A textual and attributive review, this paper is a library-based case study and historical research using qualitative method with an inductive approach.